2014
DOI: 10.1123/jsr.2012-0114
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Analysis of Selected Reach Directions of the Star Excursion Balance Test Compared With the Y-Balance Test

Abstract: Based on these observed results, the authors conclude that test performance on the SEBT and YBT differ in terms of dynamic neuro-muscular demands, as evidenced by differences in reach distances achieved in the ANT reach direction and associated test kinematic profile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 21 publications
1
73
0
6
Order By: Relevance
“…For instance, anterior-reach distance is greater and associated with less hip flexion at the point of maximal reach when executed from the ground without using a reach indicator than on the Y-Balance Test kit using a reach indicator. 29 This study provided additional insights into the LQ-YBT by highlighting that performance differences also exist between handson-hips and hands-free-to-move protocols, which are both frequently used. In future studies, researchers may seek to compare the kinematics of the LQ-YBT using the 2 hand positions to better understand the movement control of this task.…”
Section: Discussionmentioning
confidence: 89%
“…For instance, anterior-reach distance is greater and associated with less hip flexion at the point of maximal reach when executed from the ground without using a reach indicator than on the Y-Balance Test kit using a reach indicator. 29 This study provided additional insights into the LQ-YBT by highlighting that performance differences also exist between handson-hips and hands-free-to-move protocols, which are both frequently used. In future studies, researchers may seek to compare the kinematics of the LQ-YBT using the 2 hand positions to better understand the movement control of this task.…”
Section: Discussionmentioning
confidence: 89%
“…Fullam et al (Fullam et al, 2014) also found that the healthy population showed less knee flexion and ankle dorsiflexion on the SEBT compared with the YBT even though this was not statistically significant. Additionally, a previous study (Robinson & Gribble, 2008) concurred that the hip and knee joint angular displacement in the sagittal plane provided important contributions to performance in selected reach directions of the SEBT.…”
Section: Anterior Reach Directionmentioning
confidence: 91%
“…In contrast, the higher degree of accuracy observed in the detection of abnormal balance during the PM and PL reach directions are expected as these movements require the individual to implement a more complex multi-planar movement strategy. Both the PM and PL reach directions require the individual to reach outside of their base of support while utilising their trunk as a mobile counterlever, involving a combination of complex multi-planar movements occurring at the trunk, pelvis, hips, knee and ankle (Kang et al, 2015, Fullam et al, 2014. This complex multi-planar movement may more comprehensively challenge the integration of the sensorimotor subsystems, resulting in more pronounced strategy changes following the introduction of a balance deficit, thus leading to differences in the IMU data.…”
Section: Discussionmentioning
confidence: 99%
“…An additional strategy which has been employed to improve the accuracy and objectivity of the SEBT and YBT is the use of marker based motion analysis and force platform systems, providing information on the control of movement and balance strategy employed during the task (Coughlan et al, 2012, Fullam et al, 2014, Doherty et al, 2015. However, these methods have a number of major limitations, restricting their application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%